Investigation of properties of chemical anchor on the basis of epoxy resin - V. A. Shvetsova; M. G. Kovalev (Vestnik MGSU)
Introduction. With the withdrawal of foreign companies from the Russian market there is a need for domestically produced bonded chemical anchors. The properties of the first fully locally produced bonded anchor UTECH HITRE500 based on epoxy resin are studied.Materials and methods. Glass transition temperature was determined according to GOST 32618.2–2014 on the TMA Q400 device; bending strength was determined according to GOST 4648–2014, compressive strength — according to GOST 4651–2014; pullout bond strength of adhesive composition to concrete was determined according to GOST R 58387–2019 with the help of Instron 3382 testing machine.Results. The following characteristics of the bonded anchor were determined during tests: glass transition temperature, bending strength, bending elastic modulus, compressive strength, ultimate resistance of bonding resistance to breakout at operating temperatures: +23, +42, +70, –60 °С, as well as the time for which the chemical anchor gains 97.7 % breakout strength when curing at air temperature –10 °С (10 days). It was established that when the specimens cured for 1 day at room temperature are kept at temperatures of +42 and +70 °С, the ultimate pullout bond strength decreases significantly (by 29.7 and 64.7 % respectively). It was found out that when the specimens cured for 1 day at room temperature, were tested at –60 °С the pullout strength slightly increased compared to the control specimens (4.6 % higher).Conclusions. The results of tests of the first fully locally produced chemical anchor UTECH HITRE500 are presented. The glass transition temperature and physical and mechanical properties of the cured chemical anchor were determined. The time required for full bond strength gain in conditions of negative temperature –10 °C equal to 10 days was determined.